Menjadi Bodoh Karena Terlalu Pintar: Kritik dan Mistisisme dalam Kidung Cowak - Santosa, Budi (Perpustakaan Nasional RI, 2024)
“Being stupid for being too smart” is the opening verse written in Kidung Cowak. A statement with a satirical and sarcastic tone displays an unceremonious irony, delivered by the author as the opening line of his work. This is something that is not commonly found in a work of Kawi literature because almost half of the content is criticism. The author of Kidung Cowak is, by consensus, estimated to be associated with the name of Ida Padanda Sakti Talaga, who is one of Dang Hyang Nirartha’s children. Satire and sarcasm are attempts by the author to emphasize the core of his criticism. Not only does it contain criticism, but the other half of Kidung Cowak also contains various symbols about mystical and esoteric teachings that are still closely related to his criticism delivered in an euphemistic style. In addition to presenting a transcription of Kidung Cowak, this article also provides an in-depth analysis and interpretation of the text using Jürgen Habermas’s critical hermeneutics.